2018
DOI: 10.1038/s42003-018-0056-0
|View full text |Cite
|
Sign up to set email alerts
|

Multitasking of Hsp70 chaperone in the biogenesis of bacterial functional amyloids

Abstract: Biofilms are intricate communities of microorganisms embedded in a self-produced matrix of extracellular polymer, which provides microbes survival advantages in stressful environments and can cause chronic infections in humans. Curli are functional amyloids that assemble on the extracellular surface of enteric bacteria such as Escherichia coli during biofilm development and colonization. The molecular chaperone DnaK, a bacterial Hsp70 homologue, promotes curli biogenesis via unknown mechanism(s). Here we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Clp proteases involved in the degradation of misfolded proteins also showed elevated expression in biofilm stages. Several studies have proved the role of chaperone DnaK in curli-dependent biofilm formation and are considered as a potential target for anti-biofilm compounds [2325].…”
Section: Discussionmentioning
confidence: 99%
“…Clp proteases involved in the degradation of misfolded proteins also showed elevated expression in biofilm stages. Several studies have proved the role of chaperone DnaK in curli-dependent biofilm formation and are considered as a potential target for anti-biofilm compounds [2325].…”
Section: Discussionmentioning
confidence: 99%
“…Hsp70s are important for the insertion of tail-anchored proteins into the plasma membrane ( Peschke et al, 2018 ). Hsp70s prevent formation of amyloids in the cytoplasm and assist secretion of the functional amyloid curli that is necessary for biofilm formation and cell adhesion ( Evans et al, 2011 ; Sugimoto et al, 2018 ). Hsp70s are also involved in virulence of many pathogenic bacteria [for review see ( Ghazaei, 2017 )].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, DnaK was involved in the transcriptional regulation of flhDC , responsible for the flagellum biogenesis, an important organelle associated with biofilm formation, adhesion, and colonisation [ 54 ]. Moreover, a recent work by Sugimoto et al [ 55 ] showed that the DnaK protein contributes to curli formation. Via rpoS , DnaK modulates the expression of the csgDEF operon which encodes for CsgD (master transcriptional regulator of curli) acting as a positive regulator of the csgBAC operon.…”
Section: Discussionmentioning
confidence: 99%